Dominant and Subordinate Ideologies in South America: Old Traditions and New Faiths - Muratorio, Blanca (Culture, 1984)
The first part of this article discusses the dominant ideologies about the Indians of the Andean Highlands and the Amazon Basin in Colonial, post-Colonial, and contemporary times. The analysis concentrates on the “image of the Indian” or the ideological conceptions of ethnicity that emerge in the context of changing social relations among Indians, representatives of the State, dominant classes, and missionaries. Some of the anthropological approaches to the problem of ethnicity are also discussed. The second part of the article examines the attempts made by indigenous organizations to reformulate ethnicity as an oppositional ideology under present social, economic, and political conditions.